The Utilization of Nickel Slag and Oyster Shell to Improve the Concrete Strength - Selang, Sartika S.; Maryudi, Maryudi; Mufrodi, Zahrul; Widyaningrum, Sri Rahayu (Indonesian Journal of Chemical Engineering, 2024)
The increasing mining industry activity will produce increasing industrial waste. Nickel slag is one of the wastes produced from the nickel refining process by-products that have not been optimally utilized. The chemical composition of nickel slag is mostly silica with a percentage of 47.93%. Silica can be used as a material for making concrete, where a high percentage of silica is expected to strengthen the concrete structure. This study was conducted to determine the effect of nickel slag on the compressive strength of concrete and the right composition in the concrete mixture. The research method used an experimental method with different nickel slag compositions (0%, 5%, 10%, 15%, and 20%) with concrete compressive strength testing at the age of 28 days. The results of the concrete compressive strength test were that the higher the nickel slag content, the higher the compressive strength and flexural strength of the concrete. The addition of shells with different variations (0%, 5%, 10%, 15%, and 20%) showed that the best results were with the addition of 10% shells with a compressive strength of 28.1 MPa. Meanwhile, the water absorption capacity with the lowest absorption power was obtained by adding 20% ​​nickel slag, which was 8.95 %.